2021
DOI: 10.1039/d0cc06935c
|View full text |Cite
|
Sign up to set email alerts
|

Block copolymer micelles enable facile synthesis of organic–inorganic perovskite nanostructures with tailored architecture

Abstract: We report a distinct method for the production of organic–inorganic hybrid perovskite (OIHP) nanostructures using block copolymer micelles as scaffolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Nah et al reported the production of organic-inorganic hybrid perovskite nanostructure by using block copolymer micelles as scaffolds. [62] The block copolymer used as a template was PSb-P2VP which when dissolved in toluene formed a reverse micelle nanoreactor. The block copolymer micelle acted as a perovskite precursor reservoir for storing crystallization reagents.…”
Section: Miscellaneous Examples Of Copolymer Engineeringmentioning
confidence: 99%
“…Nah et al reported the production of organic-inorganic hybrid perovskite nanostructure by using block copolymer micelles as scaffolds. [62] The block copolymer used as a template was PSb-P2VP which when dissolved in toluene formed a reverse micelle nanoreactor. The block copolymer micelle acted as a perovskite precursor reservoir for storing crystallization reagents.…”
Section: Miscellaneous Examples Of Copolymer Engineeringmentioning
confidence: 99%
“…The BCP template strategies successfully produced PQDs with good optical properties, including high PLQY ranging from 50% to 90% as well as narrow emission with full width at half-maximum (FWHM) typically less than 20 nm. 15,16,43,45,47 As described by Quan and co-workers, the optical properties of BCP-templated perovskites are related to the reaction temperature and precursor ratio. 41 The PLQY increased first then decreased with the temperature ranging from −15 °C to 40 °C, with the best PLQY of 51% achieved at around 20 °C.…”
mentioning
confidence: 98%
“…41 A similar method was used for preparing MAPbBr 3 QDs in a PS-b-P2VP template, and various nanostructures were obtained by controlling the stirring rate and reaction temperature. 47 Yang and co-workers showed a facile strategy for the preparation of stable PS-b-PEO-templated MAPbBr 3 PQDs. 42 The precursor solution with PbBr 2 , CsBr and oleic acid (OA) dissolved in DMF was added dropwise into a solution of PEO-b-PS-NH 2 in toluene.…”
mentioning
confidence: 99%
See 2 more Smart Citations